PENGEMBANGAN PENILAIAN PADA JENJANG SMK - Ayu Nur Chamidah; Ulfa (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
The development of assessment at the Vocational High School (SMK) level is a strategic effort to improve the quality of vocational education in Indonesia. Assessment in SMK not only aims to measure learning outcomes but also evaluates students’ ability to apply knowledge, skills, and work attitudes required by industry standards. Assessment models such as authentic assessment, project-based assessment, and performance assessment are considered effective in measuring students’ competencies comprehensively. However, several challenges remain, including limited teacher competence in designing authentic assessments, insufficient use of digital technology, and the lack of strong collaboration between schools and industries. Therefore, enhancing teacher competence and strengthening cross-sector collaboration are necessary to create a more relevant and adaptive assessment system that produces competent graduates ready to compete in the workforce.